Head-to-Body Interval and Neonatal Outcomes After Shoulder Dystocia [A225]. (May 2022) - Antelo, Leonardo F.; Williams, Shauna; Krishnamoorthy, Kaila; Powell, Kimone A.; Apuzzio, Joseph; Gittens-Williams, Lisa
Abstract : INTRODUCTION: Shoulder dystocia (SD) is a potentially devastating emergency. Complications may result from maneuvers, yet delivery delay can result in hypoxic-related injury. Awaiting the next contraction is reported to assist in shoulder rotation. We hypothesized that shorter head-to-body delivery interval (HBI) is associated with an increase in neonatal injury without an increase in hypoxia-related sequelae. METHODS: This is a retrospective, institutional review board‒approved review of records of patients with singleton pregnancies at a tertiary-care hospital (January 1, 2015, to May 31, 2021). Patients were included if SD was documented in the delivery summary. Neonatal injury was defined as brachial plexus injury, clavicular fracture, or humerus fracture, and were compared based on HBI. RESULTS: A total of 9, 044 deliveries occurred during the study period. Of these, 71 patients were identified with SD; one was excluded. Of patients with SD, 71% had HBI <3 minutes, 90% had HBI <4 minutes, and one had HBI >6 minutes. Cord pH was available for 67% of patients, none of whom had pH <7.0. Neonatal injury was documented in 22 deliveries and was similar between HBI ≤3 minutes and >3 minutes (30% versus 42%, P =.67). Cord pH was similar with and without neonatal injury (7.177 versus 7.223, P =.069). Two infants had hypoxic injury, both with HBI >4 minutes. CONCLUSION: HBI was not associated with neonatal injury. Hypoxic injury was rare and was only seen with HBI >4 minutes. These data support allowing for maternal effort during the subsequent contraction after delivery of the head when less than 4 minutes.